Empowering Technopreneurial Leadership: Fostering Innovative Behavior among Islamic School Teachers - Rahmawati, Ima; Lestari, Hana; Sa’diyah, Zaimatus (JURNAL AL-TANZIM, 2024)
This research is motivated by the need for Islamic school's human resources who have strong character, have an entrepreneurial spirit, have high global insight competence, can think critically, creatively, communicatively, collaboratively, and innovatively, and have academic abilities that are in line with organizational needs in the era of digitalization. This means that madrasah teachers who have innovative work behavior are needed. To develop creative work behavior, a leader who can manage madrasa human resources must integrate entrepreneurial values with technology. The focus of the problem in this research is to develop a school principal's Technopreneurship leadership model to develop teachers' innovative work behavior influenced by self-efficacy, work environment, and teacher adaptability. The approach used in this research was a combination store using an explanatory method, and the research sample was 156 Bogor City Private MA teachers. Data was collected using questionnaires using a Likert scale, interviews, observation, documentation, and FGD. It was analyzed using the SmartPLS Ver 2.0 and Atlas TI evaluation models. The research results show that the technopreneur-ship leadership model can develop innovative work behavior in Islamic school teachers. So, suppose the school principal's Technopreneurship leadership model is implemented. In that case, it will impact increasing the innovative work behavior of Islamic school teachers, which will indirectly improve the quality of Islamic school education, marked by the formation of a professional Islamic school ecosystem.